1994
DOI: 10.1093/hmg/3.10.1763
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the human mitochondrial transcription factor h-mtTFA in infantile mitochondrial myopathy is associated with mtDNA depletion

Abstract: Recent studies show that patients presenting with cytochrome oxidase (COX) deficiency in infancy may have reduced mitochondrial DNA (mtDNA) in muscle. The human mitochondrial transcription factor A (h-mtTFA) may be an important regulator of both transcription and replication of mtDNA. h-mtTFA levels were investigated in cell lines which were either free of mtDNA (rho 0) or temporarily depleted by treatment with dideoxycytidine (ddC), and in tissue from three patients with mtDNA depletion and cytochrome oxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(94 citation statements)
references
References 0 publications
5
88
0
Order By: Relevance
“…TFAM levels, in contrast with mtSSB or POLG and POLG2 levels, were severely reduced. This agrees with previous studies showing a strong correlation between TFAM protein levels and mtDNA levels, using rho-zero cell lines, cell lines partially depleted by dideoxycytidine treatment, material from patients suffering from mtDNA depletion and heterozygous TFAM knockout mice (Larsson et al, 1994;Poulton et al, 1994;Larsson et al, 1998). This strongly suggested that TFAM protein stability and turnover depends on its interaction with mtDNA and is supported by our observation of an apparent dependence of the occurrence of TFAM degradation products on a lack of DNA binding.…”
Section: Mitochondrial Nucleoids In Human Cells Are Assemblies Of Mulsupporting
confidence: 93%
“…TFAM levels, in contrast with mtSSB or POLG and POLG2 levels, were severely reduced. This agrees with previous studies showing a strong correlation between TFAM protein levels and mtDNA levels, using rho-zero cell lines, cell lines partially depleted by dideoxycytidine treatment, material from patients suffering from mtDNA depletion and heterozygous TFAM knockout mice (Larsson et al, 1994;Poulton et al, 1994;Larsson et al, 1998). This strongly suggested that TFAM protein stability and turnover depends on its interaction with mtDNA and is supported by our observation of an apparent dependence of the occurrence of TFAM degradation products on a lack of DNA binding.…”
Section: Mitochondrial Nucleoids In Human Cells Are Assemblies Of Mulsupporting
confidence: 93%
“…For example, overexpression of let-7 inhibits Lin28, induces insulin resistance, and impaired glucose tolerance in skeletal muscle (31). As occurs in myogenic C2C12 cells, endurance exercise significantly downregulates miR-494 and upregulates its target genes mtTFA and forkhead box j3 (30) that have been shown to play important roles in mitochondrial biogenesis (34,35). Transgenic mice overexpressing miR-23a displayed by immunoblot 48 h after transfection.…”
Section: Discussionmentioning
confidence: 99%
“…While decreased mtDNA content was invariably detected in affected tissues, nonaffected tissues exhibited a wide range of mtDNA abundance levels. For example, in a patient who presented with neonatal encephalopathy and expired in infancy muscle mtDNA content was 23%, liver 7%, kidney 24%, and brain 37% of the control (14). It is a matter of conjecture whether organs such as kidney or muscle would become involved had this patient lived longer, given the known variability of clinical threshold among tissues (15).…”
Section: The Metabolic Disease Unit Shaare-zedek Medical Center Andmentioning
confidence: 99%
“…A search for mutations in the Tfam gene was initiated by the finding of decreased abundance of the Tfam protein in the cells of several patients with mtDNA depletion but none were found. Thus, in the study of candidate genes, proteins that require mtDNA molecules for their own stability and are secondarily decreased, should be distinguished from those that are the primary cause of the disease (14,52).…”
Section: The Metabolic Disease Unit Shaare-zedek Medical Center Andmentioning
confidence: 99%